PENGARUH EARNING PER SHARE, DIVIDEND PER SHARE DAN FINANCIAL LEVERAGE TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mortigor Afrizal Purba (LPPM Universitas Putera Batam, 2019)
The stock price describes the performance of the company. The better the performance of the company, the higher the stock price. Therefore the company needs to maintain the company's performance so that the stock price does not decline continuously every year. One way to find out that the company has good corporate performance by comparing the company's financial ratios from the previous year to the following year. The aim of this study is to examine the effect of EPS, DPS, and Financial Leverage on the stock prices of food and beverage companies listed on the Indonesia Stock Exchange 2014-2018. The population in this study amounted to 18 food and beverage companies with the period 2014-2018. While the sample selected using the purposive sampling method with a total of 9 companies for 5 years processed data as many as 45 data. Data tested using basic assumptions, classic assumption tests, multiple linear regression tests and hypothesis testing. The results of the study show that EPS, DPS, and Financial Leverage simultaneously have a significant effect on stock prices. While partially EPS has a significant effect on stock prices, DPS has no significant effect on stock prices, and Financial Leverage also does not have a significant effect on stock prices.